Conformational restriction of a type II FMS inhibitor leading to discovery of 5-methyl-N-(2-aryl-1H-benzo[d]imidazo-5-yl)isoxazole-4-carboxamide analogues as selective FLT3 inhibitors. (1st January 2019) - Im, Daseul; Moon, Hyungwoo; Kim, Jingwoong; Oh, Youri; Jang, Miyoung; Hah, Jung-Mi
Abstract: A series of 4-arylamido 5-methylisoxazole derivatives incorporating benzimidazole was designed and synthesised by conformational restriction of an in-house type II FMS inhibitor. Kinase profiling of one compound revealed interesting features, with increased inhibitory potency towards FLT3 and concomitant loss of potency towards FMS. Several benzimidazole derivatives 5a–5g and 6a–6c containing various hydrophobic moieties were synthesised, and their inhibitory activity against FLT3 was evaluated. Specifically, 5a, 5-methyl- N -(2-(3-(4-methylpiperazin-1-yl)-5-(trifluoromethyl)phenyl)-1 H -benzo[d]imidazole-5-yl) isoxazole-4-carboxamide, exhibited the most potent inhibitory activity against FLT3 (IC50 = 495 nM), with excellent selectivity profiles.